Influence of the number and geometry of binding sites on host-guest affinity: Imidazolium-substituted receptor molecules for small inorganic anions - Fahlbusch, Tilmann; Frank, Markus; Schatz, Jürgen; Schmaderer, Harald (European Journal of Organic Chemistry, 2006)
The influence of the number and relative geometry of the binding sites on the binding of spherical and tetragonal inorganic anions (Cl , Br , H PO , and HSO ) has been studied by using imidazolium salts based on benzene and calix[4]arenes. Binding constants in DMSO were found to be in the range of 200-2000 L mol . Three or four binding sites (2b-4b) lead to the nonselective binding of all anions indicating the decisive influence of the number of possible binding positions; binding constants of approximately 2000 for H PO , 1000 for HSO , 900 for Cl , and 800 L mol for Br were obtained. Benzene- (1b) and calixarene-based (5b) bis(imidazolium) salts exhibited a high selectivity towards H PO / HSO and Cl /Br indicating that for the complexation of H PO and Cl two binding sites are necessary, and for Br and HSO at least three. In this case, selectivity could be obtained by simple variation of the number of identical binding positions. © Wiley-VCH Verlag GmbH & Co. KGaA, 2006.